Deconstructing and implementing high-leverage teaching practices with the integrated communicative approach: an instructional design framework for teaching novice learners in the secondary world language classroom - Ahnell, Sara Walker (Kansas State University, 2023)
High-Leverage Teaching Practices (HLTPs) are identifiable core practices that a teacher must be able to execute to bring about effective learning in the classroom. World language education has its own content specific HLTPs, but secondary world language teachers are challenged with the responsibility of integrating these HLTPs along with state and national standards, proficiency goals, and authentic resources into their instruction for Novice learners, all while staying in the target language. Creating instruction for Novice learners is inherently more difficult than creating instruction for learners of higher levels of language proficiency because the limited linguistic ability of beginners necessitates more structured and scaffolded instruction for the sake of comprehensibility. Because of the complexity of the demands of instructional design in a world language classroom, especially for Novice learners, it is clear that a comprehensive instructional approach would benefit the pedagogical content knowledge (PCK) of both pre-service and in-service teachers who teach these learners. The ideal approach would be structured and prescriptive enough to consistently provide appropriate scaffolding and support to learners and be effective in aiding the teacher to design and implement contextualized, comprehensible instruction without sacrificing creativity. I conducted a content analysis to determine if such an instructional approach existed. I chose a sample region of the United States to investigate the instructional design resources available on state department websites and several commercially available language education methods textbooks for 6-12 world language teachers. None of the resources, including state department documents from the SCOLT region, national standards, ACTFL Website articles, or language teacher preparation publications, proposed or advocated for any specific instructional approach except the PACE model used to teach grammar in a dialogic context. While this lack of a defined framework allows teachers total freedom in creating their instructional materials, world language teachers looking for clear guidance in creating effective instruction in the target language are left without recourse. To remedy the absence of any framework for teaching Novice learners and integrating HLTPs for language learning, this study presents a new approach to creating world language instruction for Novice learners called The Integrated Communicative Approach (ICA). This approach integrates HLTPs for language learning into proficiency-based, culturally authentic, contextualized instruction while simultaneously creating a pseudo-immersion environment for Novice learners in the secondary classroom. The approach begins with the creation of a standards-based, contextualized performance assessment and continues with explanations and examples of models for four different lesson types that comprise an ICA unit created using backward design: (1) the CIMO model for vocabulary-focused lessons, (2) the CI(G)MO model which combines the structure of processing instruction and the whole language approach of the PACE model for teaching grammar, (3) the PGAP model for literacy focused instruction using authentic resources, and (4) the ABCC, a model for the study of an artifact from the target culture to explore products, practices, and perspectives. Based on the approach presented in this study, pre-service and in-service world language teachers may gain new insight into instructional design and practical tools for designing and implementing proficiency-based, contextualized language instruction for Novice learners.
Keywords: World language education; High-leverage teaching practices; Instructional framework; Contextualized language instruction